2021
DOI: 10.3390/su132011148
|View full text |Cite
|
Sign up to set email alerts
|

Training Conditions and Emotional Impact on Spanish Olympic Swimmers and Rowers in Social Isolation Due to COVID-19. Results of a Survey

Abstract: This article analyzes the results of a survey conducted in 2020 with Spanish Olympic swimmers and rowers, who were confined to their homes due to the epidemiological crisis. The questionnaire was administered between 23 April and 25 May. Responses to the questionnaire on emotional and adaptive reactions during the COVID-19 confinement (REACOVID-19) were received from 88 subjects, who represented 100% of the total population of Spanish Olympic swimmers and rowers. Through this questionnaire, they were asked abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…However, it must be acknowledged that despite the cancellation of competitions and changes in training conditions, the athletes remained generally positive, and it was hoped that the pandemic would have a modest impact on Estonian sports [ 14 ]. A similar result was obtained by Moscoso-Sanchez et al [ 9 ], who studied the swimmers and rowers who represented Spain at the Olympic Games.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, it must be acknowledged that despite the cancellation of competitions and changes in training conditions, the athletes remained generally positive, and it was hoped that the pandemic would have a modest impact on Estonian sports [ 14 ]. A similar result was obtained by Moscoso-Sanchez et al [ 9 ], who studied the swimmers and rowers who represented Spain at the Olympic Games.…”
Section: Introductionsupporting
confidence: 86%
“…The restriction period caused significant changes in athletes’ training routines [ 6 ], and although efforts were made to maintain physical activity, several studies showed a reduction in athletes’ training frequency, duration [ 7 ] and intensity, mostly because athletes and their coaches did not have enough time to prepare training programs for in-home training [ 8 ]. For example, 50% of swimmers and rowers on the Spanish Olympic team said that despite being able to take advantage of home training conditions, they lost quite a lot or a lot of their physical fitness during the isolation period [ 9 ]. Decreased physical activity had a negative effect on athletic performance, which in turn increased stress levels and created negative mood states [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it cannot readily be concluded that differences between team sports and individual sports would be the same in a country applying less mandatory COVID-related restrictions, such as Sweden, as in countries with clear lockdown procedures. Indeed, the reporting of lifestyle changes and mental health impact has in some literature focused on proper lockdown procedures (Martínez-Patiño et al, 2021 ; Moscoso-Sánchez et al, 2021 ), which were not implemented in Sweden during any phase of COVID-19. However, in the Swedish setting, one would intuitively assume that individual sports would go less affected by anti-virus recommendations against public gathering which would instead have a substantial impact on team sports and their match events or major tournaments.…”
Section: Discussionmentioning
confidence: 99%
“…Other scholars have reported similar results. Maintaining physical activity, the availability of sports equipment and possibility to continue with training were, for example, reported as protective for Spanish elite athletes' mental health during lockdown (Jaenes Sánchez et al, 2021 ; Moscoso-Sánchez et al, 2021 ). Jaenes Sánchez et al ( 2021 ) also found that acceptance of the need of social isolation during the pandemic was related to positive feelings like friendship.…”
Section: Discussionmentioning
confidence: 99%